FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PETANI KELAPA SAWIT RAKYAT BERPARTISIPASI DALAM SERTIFIKASI PRODUK DI KABUPATEN KAMPAR - Rizka Emilia; Sakti Hutabarat; Arifudin Arifudin (Universitas Sebelas Maret, 2014)
Oil palm product certification consists of the Roundtable of Sustainable Palm Oil (RSPO) and the Indonesian Sustainable Palm Oil (ISPO). RSPO certification is a voluntary certificate that must be met by oil palm mills to sell their products in international market. ISPO is a mandatory certificate that must be comply by grower and miller which operate their bisnis in Indonesia. A number of principles and criteria must be comply by smallholders to obtain RSPO certificate. The objective of this study is to analyse farmer perception and factors that influence smallholder participation in certification in Kampar Regency. The population of this study are scheme smallholders (NES/KKPA) and independent smallholders. This study use Summated Likert scale rating to evaluate farmers’ perception and binary logistic regression to assess smallholders participation. The results show that certification is very important while it is important for independent smallholders. Education and land size are factors that influnce scheme smallholders in participating in certification while eduction, land size and job are factors that influence independent smallholders.